Prevalence and risk factors of myopic maculopathy: a cross-sectional study in Han and Uygur adults in Xinjiang, China - Ke Wang; Jin Ma; Yong Zhong; Ting Chen; Fen Dong; Lin Ding; Guang-Liang Shan; Lize Pa; Limujiang Ke; Hebuli Mu; Senjiang Ya; Ning Tao (BMJ Open)
Objectives To estimate the prevalence, ethnic differences and associated risk factors of myopic maculopathy in Han and Uygur adults in Xinjiang, China.Design and setting A cross-sectional study with multistage, stratified cluster sampling method was conducted in Xinjiang, China.Participants A total of 4023 Han and Uygur participants aged 40 years and older were eligible for the study.Outcome measures The association between myopic maculopathy and its risk factors was screened using the generalised estimating equation (GEE) model. We also investigated whether ethnic differences exist between Han and Uygur populations affected by myopic maculopathy. Myopic maculopathy was defined in accordance with International Photographic Classification and Grading System for Myopic Maculopathy.Results A total of 3044 subjects (5946 eyes) were included in our study (1736 Han and 1308 Uygur individuals). The participants consisted of 1256 (41.3%) men and 1788 (58.7%) women. The average age was 52.2±9.4 years, and the mean spherical equivalent (SE) was −0.18±2.31 dioptre (D). Myopic maculopathy was detected in 198 eyes of 138 participants. The age-adjusted prevalence of myopic maculopathy reached 5.8% (95% CI 4.8 to 6.8). In the GEE model, myopic maculopathy was significantly associated with old age (per year; OR: 1.16; 95% CI 1.13 to 1.19; p<0.001) and myopic SE (per −1 D; OR: 1.48; 95% CI 1.40 to 1.56; p<0.001). No ethnic differences were detected between Han (98, 5.7%) and Uygur population (40, 3.1%) in terms of the prevalence of myopic maculopathy (OR=0.89; 95% CI 0.53 to 1.48; p=0.64). Neither urbanisation (p=0.38) nor the level of education (p=0.92) was associated with myopic maculopathy.Conclusions A high age-adjusted prevalence of myopic maculopathy was observed in Han and Uygur populations in Xinjiang, China. Old age and high degree of myopic refraction were independent risk factors for myopic maculopathy. No ethnic differences were detected in Han and Uygur populations affected by myopic maculopathy.